Circularity and LCA - material pathways: the cascade potential and cascade database of an in-use building product. Issue 1 (1st December 2022) - Schaubroeck, Simon; Dewil, Reginald; Allacker, Karen
Abstract: Improving circularity in the building sector entails ensuring greater material efficiency to avoid virgin material extraction. To assist stakeholders in decisions regarding salvaging an in-use building product, the potential further uses of this salvaged product and its materials should be determined. In other words, its cascade potential should be determined given circular strategies, i.e. to reuse, repurpose, repair sequentially. To predict the cascade potential, a database is required that combines (acquired) product data, assembly characteristics and process data, e.g., info on the process to melt old steel. This database is referred to as a cascade database. The aim of this research is to study steps to form this database, specifically, the combination of product passports and an LCA process database. Hereto, major existing European data tools are considered. For product data, material passports and digital product passports initiatives are identified and compared. For process data, LCA databases are considered. Interactions between these data tools are a possible way to set up a partial cascade database. A workflow is then described- on how to acquire data on the cascade potential of a product from such a database. We note that the cascade database also relies on extensive (economic) forecast models, data collection and stakeholder interaction. Setting up such an extensive database and generating all possible cascading paths is a challenging, if not unachievable, feat. Nevertheless, even limited applications of this database might help reach a more circular economy.